Ethnobotany of priority food and medicinal plant species of the Anacardiaceae family in the subequatorial area of Benin - Togni, Yolande; Ganglo , Jean Cossi (Ethnobotany Research and Applications, 2025)
Background: This study was conducted to assess the use value of priority food and medicinal plant species of the Anacardiaceae family in the sub-equatorial area of Benin. Methods: Data were collected through a literature review and an ethnobotanical survey. Eight criteria and four prioritization methods were used. The ethnobotanical study was based on questionnaires administered to 194 respondents. Citation frequencies, Use diversity value (UDs), Use equitability value (UEs), Ethnobotanical Use Value (UV) were calculated. Results: 14 species were identified. Among them, Lannea nigritana (Scott-Elliot) Keay, Sorindeia grandifolia Engl. and Spondias mombin L. were priority food and medicinal species for conservation in the area. The predominant forms of use were wood energy and fodder for L. nigritana, chewing stick for S. grandifolia, the direct consumption of fruit and fodder for S. mombin. The Use Diversity (UDs) and Use Equitability (UEs) values of plant species revealed that men and women share similar knowledge levels, younger individuals possess less understanding, and traditional practitioners demonstrate advanced knowledge of S. mombin and its uses. S. mombin had the highest ethnobotanical use value (UV = 5,33). Gender (L. nigritana (p ˂ 0.000); S. mombin (p = 0.0009)) and the profession (L. nigritana (p ˂ 0.000); S. mombin (p = 0.002)) had a significant effect on the ethnobotanical use value of L. nigritana and S. mombin . Conclusions: For the conservation of these species, raising public awareness should be used to encourage sustainability practices. Keywords: Anacardiaceae, species prioritization, food and medicinal species, conservation